2021
DOI: 10.3390/s21093090
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Mobility during the COVID-19 Pandemic and Its Association with Increase in Depression among Older Adults: A Longitudinal Remote Mobility Monitoring Using a Wearable Sensor

Abstract: Background: Social isolation during COVID-19 may negatively impact older adults’ wellbeing. To assess its impact, we measured changes in physical activity and sleep among community-dwelling older adults, from pre-to post-pandemic declaration. Method: Physical activity and sleep in older adults (n = 10, age = 77.3 ± 1.9 years, female = 40%) were remotely assessed within 3-month pre-to 6-month post-pandemic declaration using a pendant-wearable system. Depression was assessed pre-and post-pandemic declaration usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 31 publications
(63 reference statements)
2
57
0
1
Order By: Relevance
“…Heterogeneity in the study types was observed as follows: cross-sectional (n = 9; 53%), longitudinal (n = 4; 24%), retrospective (n = 1; 6%), narrative review (n = 1; 6%) and pilot non-randomized studies (n = 2; 12%). Similar heterogeneity was found in participants too in the included studies: pregnant women [27], elderly [24,26], office workers [21], diabetes [18] and children [25]. All the studies were from high-income countries.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Heterogeneity in the study types was observed as follows: cross-sectional (n = 9; 53%), longitudinal (n = 4; 24%), retrospective (n = 1; 6%), narrative review (n = 1; 6%) and pilot non-randomized studies (n = 2; 12%). Similar heterogeneity was found in participants too in the included studies: pregnant women [27], elderly [24,26], office workers [21], diabetes [18] and children [25]. All the studies were from high-income countries.…”
Section: Resultssupporting
confidence: 59%
“…Seven studies administered smartphone-based physical activity measurement through inbuilt accelerometers from which the captured data were transferred to the cloud server and visualized in smartphone applications [16-19, 21, 24, 31]. Majority of studies (n = 9; 53%) employed wrist bands and wristwatches of multiple technology firms (Apple, Samsung, Xiaomi) and wearable research-based accelerometers [20,23,25,26,[28][29][30]32]. A few studies (n = 4; 24%) reported the psychometrics of the wearables, and lowto-moderate validity was found [21,22,27].…”
Section: Wearables and The Measurement Of Physical And Physiological Variablesmentioning
confidence: 99%
“…Mishra et al [23] investigated the impact of social isolation during the COVID-19 pandemic on wellbeing in older adults. There were a total of 10 adults who were aged ≥75 years or ≥65 years with a risk of falling.…”
Section: Physical Activity During the Covid-19 Pandemicmentioning
confidence: 99%
“…The pandemic has led to a decrease in PA in older adults [ 56 , 57 ], as well as an emphasis on the importance of older adults with cancer minimizing outings and observing physical distancing [ 24 ]. While an increasing proportion of older adults are being vaccinated, COVID infections due to new variants are rising, and the pandemic may continue into the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%